Cultivation of Anthurium Flower Plant in Sewu Kembang Tourism Village, Nglurah, Tawangmangu - Hidayatun Nurul Khasanah; Antik Murwani; Rahmadani Rahmadani; Rif'atin Khoirunnisa; Riska Satya Graha Putrimulya; Umi Salamah; Hania Nurbayti; Farhah Qurrotu 'Aini; Avivi Khoirunnida; Qurota A'yun; Nur Rokhimah Hanik (Jurnal Biologi Tropis, 2023)
Anthurium flower is an ornamental plant that is widely known and favored by plant lovers. Apart from being a beautiful plant, anthurium is a type of ornamental plant that is easy to care for and cultivate. The purpose of this research is to get anthurium crosses with better variations and to understand proper care and cultivation methods. This research was conducted in the Sewu Kembang Tourism Village, Nglurah Tawangmangu. Data collection in this study was carried out using observation and interview methods. The research data was then analyzed by descriptive qualitative. From the results of the research that has been done, data is obtained showing that anthurium plant propagation can be done in two ways, namely generative and vegetative. In cultivating anthurium, factors that need to be considered include tools and materials, nurseries, and planting methods. Then in the care of anthurium things that must be considered are watering, fertilizing, weeding, placement, repotting, and pest and disease control.